2022
DOI: 10.1007/s13762-022-04715-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification kinetics, N2O emission, and energy use in intermittently aerated hybrid reactor under different organic loading rates

Abstract: This study investigated the impact of intermittent aeration strategies and reduction in the reactor’s organic and nitrogen loading rates on the course of particular stages of the nitrification process, as well as energy consumption and N2O emissions in a hybrid reactor with nitrification/denitrification. Each of the analysed series revealed the greatest ammonia oxidation activity in activated sludge flocs. The highest activity of nitrite nitrogen oxidation was demonstrated in the case of biofilm. A reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…S.II.1.). This aligns with the observations made for the biofilm from hybrid systems [17,18]. Data presented in Figure 5 also suggest that irrespective of the research stage, nitriteoxidizing bacteria showed greater activity, which is consistent with qPCR results, where NOB were the predominant bacterial group in all samples.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...supporting
confidence: 90%
See 3 more Smart Citations
“…S.II.1.). This aligns with the observations made for the biofilm from hybrid systems [17,18]. Data presented in Figure 5 also suggest that irrespective of the research stage, nitriteoxidizing bacteria showed greater activity, which is consistent with qPCR results, where NOB were the predominant bacterial group in all samples.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...supporting
confidence: 90%
“…The analysis of the data collected from batch tests shows that changes introduced in MBSBBR operation parameters had a greater effect on the activity of ammonia-oxidizing bacteria. Previous studies also reported that the activity of ammonia oxidizers was more susceptible to changes in system operation than those capable of oxidizing nitrite [17,18]. It is worth emphasizing that in that case, the biofilm came from a hybrid reactor, where, next to this form of biomass, also activated sludge developed.…”
Section: Nitrification Kinetics and Nitrifier Diversity In The Moving...mentioning
confidence: 90%
See 2 more Smart Citations